Deteksi fraudulent financial reporting: suatu pendekatan menggunakan accrual based investment ratio dan cash based investment ratio - Devanus Abelingga; Pratana Puspa Midiastuty; Eddy Suranta; Rini Indriani (Jurnal Akuntansi, Keuangan, dan Manajemen, 2021)
Purpose: This study aimed to provide empirical evidence of the influence of Accrual Based Investment Ratio and Cash-Based Investment Ratios in detecting fraudulent financial reporting Research methodology: Fraudulent financial reporting in this study used a combined model of the cheating model (Beneish M-Score) with a bankruptcy model (Altman Z-Score). This study's sample was a non-financial company listed on the Stock Exchange during the observation period from 2010-2018. Sampling techniques with purposive sampling and obtained a total of 790 observations. Data processing was done via SPSS program version 16.0 using logistic regression. Results: This study proves that Earnings per Share, Dividend per Share ratio, Total Share Profitability Ratio, Dividend Profitability, Asset Efficiency Ratio influence in detecting fraudulent financial reporting while Price / Earning ratio, Dividend Ratio, Operating Cash Flow Ratio, Current Liability Coverage Ratio, Long Term Debt Coverage Ratio, Interest Coverage Ratio, Cash Generating Power Ratio, External Financing Index Ratio do not affect detecting fraudulent financial reporting Limitations: There are still inaccuracies in predicting Fraudulent Financial Reporting so that for future research, other combined models can be used in predicting Fraudulent Financial Reporting, including adding liquidity ratios, asset management ratios, debt management ratios, profitability ratios, and sufficiency ratios Contribution: This study provides implications for the signal theory that explains the usefulness of financial statements in decision making and predictions, including using financial ratios in predicting Fraudulent Financial Reporting Keywords: Fraudulent financial reporting, Accrual based investment ratio, Cash-based investment ratio, Beneish M-Score, Altman Z-score